The Implementation of Nucu Ngoruh in The Traditional Marriage of The Dayak Siang Tribe - Alexandro, Rinto; Pernandes, Pernandes; Karliani, Eli; Hariatama, Fendy; Uda, Tonich (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze the implementation, support, and inhibiting factors of nucu ngoruh in Dayak Siang traditional weddings. A qualitative method with observation, interviews, and documentation was utilized to get the research finding. The implementation of nucu ngoruh in traditional Dayak Siang marriages in Saripoi Village consisted of two versions. The first version of the wedding procession was making pondong, making lawang sakepeng, making hompong, and the marriage contract process. The second version of the marriage procession was pantan pulut, pali manasai, ngiap or kandan ngiap, second hompong and third hompong, which includes hompong balanga, lawang sakepeng, Manasai dance, hompong human/female, and the bride and groom sat side by side on the Mura gong. The supporting factor for nucu ngoruh was that indigenous peoples highly respected the provisions of social and divine values, so indigenous people adjusted to the provisions for the preparation of traditional goods, and the procession of traditional marriages might also be under customary rules. Finally, there were four inhibiting factors for nucu ngoruh. First, the groom was not ready either physically or mentally. The second was the lack of financial support provided. The third was the absence of people who mastered the art of sculpture was make statues to complete the implementation of the traditional Dayak Siang wedding. Fifth, there was no written text or manual procedure for implementing the traditional Dayak Siang wedding procession.